Fabrication of Electrospun Nanofibres of Soy Protein Isolate/Polyvinyl Alcohol Embedded with Cinnamon Zeylanicum and Zataria Multiflora Essential Oils and their Antibacterial Effect - Raeisi, Mojtaba; Mohammadi, Masoud Aman; Bagheri, Vahid; Ramezani, Soghra; Ghorbani, Marjan; Tabibiazar, Mahnaz; Noori, Seyyed Mohammad Ali (AMG Transcend Association, 2023)
The current study aimed to develop edible nanofibrous films embedded with essential oils (EOs) by the electrospinning method and assess their antimicrobial activity. At first chemical components of Cinnamon zeylanicum (Cz) and Zataria multiflora (Zm) EOs were evaluated, and their antimicrobial activities were investigated. Then, Cz and Zm EOs were added to Soy Protein Isolate (SPI)/Polyvinyl alcohol (PVA) by the electrospinning method. SEM, FTIR, and TGA tests were carried out to investigate the characteristics of fabricated nanofibers. The antimicrobial properties of nanofibers were investigated. SEM exposed that adding 50% PVA neutralized SPI charge, conducive to a significant decrease in nanofibers diameter by 130 nm. Moreover, TGA displayed SPI-PVA nanofibers' stability. Developed nanofibers showed excellent antimicrobial effects toward Gram-positive and-negative pathogens. For instance, SPI-PVA nanofibers containing 20% Cz reduced 72, 56, and 42% S. aureus, B. cereus, and S. typhimurium. However, in the case of E. coli, Zm showed the best result and reduced 42% of the bacterium. In gist, nanofibrous films containing Cz and Zm EOs can be utilized in active food packaging to increase the durability of food due to their excellent antimicrobial activity. © 2023 by the authors. This article is an open-access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https://creativecommons.org/licenses/by/4.0/).
Keywords: active food packaging; active food packaging; bioactive film; essential oil; nanotechnology and nanofiber